Bahasa Gaul Dan Pengaruhnya Terhadap Penggunaan Bahasa Indonesia - Dariz Radyananda Barus; Sinta Engelika; Sasti Permata; Balqis Balqis; Veri Febrian; Fitriani Lubis (Asosiasi Periset Bahasa Sastra Indonesia, 2023)
Language is very important for human life because through it they can communicate with each other. Language is also used to communicate one's ideas, concepts, opinions, feelings and thoughts to other people. as well as a tool for personal growth and interaction with others. This research aims to find out how important it is to use Indonesian properly and correctly, what causes the widespread use of slang, especially among teenagers, and how slang influences the use of Indonesian. In processing the data in this article, the literature study method was used to study various literature. Slang has caused the decline of good and correct Indonesian language martabak. Today's society has been influenced by technological advances which have triggered the emergence of slang. National identity and Indonesian as an official language must be strengthened so that it is not influenced by slang.